2010
DOI: 10.4269/ajtmh.2010.10-0078
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Chicken Seroconversions Track Tangential Transmission of West Nile Virus to Humans in the Greater Los Angeles Area of California

Abstract: In Los Angeles, California, West Nile virus (WNV) has followed a pattern of emergence, amplification, subsidence, and resurgence. A time series cross-correlation analysis of human case counts and sentinel chicken seroconversions revealed temporal concordance indicating that chicken seroconversions tracked tangential transmission of WNV from the basic passeriform-Culex amplification cycle to humans rather than antecedent enzootic amplification. Sentinel seroconversions provided the location and time of transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Each surveillance method provides unique information about viral activity in the vector and host populations; dead birds inform control agencies about the location and magnitude of virus activity, testing of Our results for the timeliness of detection showed that mosquitoes and dead birds generally detected virus activity earlier than nearby sentinel chicken flocks when sampling frequency and spatial density were equalized. Our findings agree with those of several studies, which showed infection in mosquitoes and WNV-positive dead birds preceded sentinel chicken seroconversion by 1-2 weeks (Cherry et al 2001, Patnaik et al 2007, Unlu et al 2009, Kwan et al 2010. Part of this lag in detection by sentinel chickens may be due to the delay between the infectious mosquito bite and the time when antibodies become detectable by ELISA in the sentinel chickens, which can be 7-10 days after the infectious bite (Senne et al 2000, Patiris et al 2008.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Each surveillance method provides unique information about viral activity in the vector and host populations; dead birds inform control agencies about the location and magnitude of virus activity, testing of Our results for the timeliness of detection showed that mosquitoes and dead birds generally detected virus activity earlier than nearby sentinel chicken flocks when sampling frequency and spatial density were equalized. Our findings agree with those of several studies, which showed infection in mosquitoes and WNV-positive dead birds preceded sentinel chicken seroconversion by 1-2 weeks (Cherry et al 2001, Patnaik et al 2007, Unlu et al 2009, Kwan et al 2010. Part of this lag in detection by sentinel chickens may be due to the delay between the infectious mosquito bite and the time when antibodies become detectable by ELISA in the sentinel chickens, which can be 7-10 days after the infectious bite (Senne et al 2000, Patiris et al 2008.…”
Section: Discussionsupporting
confidence: 93%
“…During the past two decades, most sentinel chicken flocks have included seven to ten chickens per flock (Reisen et al 1992a, Reisen et al 2000, Cherry et al 2001, Scott et al 2001, Reisen et al 2004, Kwan et al 2010, with a flock size of 10 chickens recommended by the CDPH (California Department of Public Health et al 2013). This was preceded by a period through the early 1990s when 25 chickens was the typical flock size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the use of sentinel animals is instrumental in identifying and monitoring areas with a high density of insect sites. Chickens have been used as sentinel animals for viral diseases transmitted by insect bites through the monitoring of anti-viral antibody responses891011.…”
mentioning
confidence: 99%
“…In Los Angeles, 65 and perhaps elsewhere in California, 66,67 chicken seroconversions usually lagged behind other measures of virus activity such as mosquito infection and dead bird data and may track spill over events concurrent with tangential infection of humans. These data indicated that WNV amplification may begin and proceed under R 0 values 1 and precede the transmission events depicted here that may parallel spill over events and increased risk for human infection.…”
mentioning
confidence: 99%